The Correlational Analysis of Motivation and Productivity of Librarians in Public Universities in Nigeria - AbdulazeezYaya, Japheth; EurielUzohue, Chioma; Akintayo, Oluseyi A. (IJRDO- Journal of Educational Research, 2016)
This study investigated the relationship between motivation and productivity of librarians in Nigerianpublic universities. A correlational survey research design was adopted. The study population consistedof 1,254 librarians in public university libraries in Nigeria, from which 923 were selected using simplerandom sampling. The research instrument used was a self-developed questionnaire. The study revealeda significant relationship between motivation and productivity (r = 0.035, P < 0.05) of librarians in publicuniversity libraries in Nigeria. It concluded that contrary to general belief, motivation and productivitylevels of librarians in university libraries were high. It is recommended that university librarymanagement should continue to promote values such as improved employee recognition, good leadershipstyle and improved employees’ motivational programmes that would increase productivity of itsworkforce.